Factors affecting detection probabilities of acoustic transmitters using passive receivers - William J. Radigan; Cali Engel; Phil Chvala; Christopher Longhenry; Mark Pegg (Animal Biotelemetry)
Abstract Background Passive acoustic telemetry is a common tool used to study fish movements. Range tests, or determining the distance at which transmitters can be recognized by a receiver, are needed to accurately determine fish position in the environment. However, range tests are not often conducted or are only completed during a single season prior to an acoustic telemetry study commencing though seasonality may affect detection probabilities over a multi-year study’s duration. Therefore, we conducted a series of tests to assess the effect of seasonality on range detection over a 3-year period on Lewis and Clark Lake, a Missouri River reservoir. Specifically, we measured the effects that seasonal environmental (e.g., wind, depth, temperature) factors had on detection probability at a range of distances using Innovasea V13 acoustic transmitters at 14 VR2tx 69-kHz passive receivers. These data were used to inform array design for a concurrent acoustic telemetry research project. We accounted for spatiotemporal variation in detection probability by evaluating monthly detection probabilities across years from March–September during 2022–2024. Results Mean detection probability for Lewis and Clark Lake receivers from range tests was 0. 60 for 50 m, 0.50 for 100 m, 0.37 for 200 m, 0.23 for 400 m, 0.15 for 600 m, and 0.11 for 800 m. We found detection probabilities in the spring were greater than those in the other seasons. We found negative relationships between detection probabilities and distance between the tag and receiver, wind speed, inflow through Fort Randall Dam, and tag depth. Further, we found detection probabilities varied with river kilometer, presumably due to habitat differences. Conclusions Implications of our findings include consideration of lower realized detection probabilities (i.e., resulting from environmental factors) compared to equipment capabilities during study design, and the consideration of both anthropogenic influences (i.e., inflow) and natural environmental factors (i.e., wind) that affect detection probabilities. The receiver array in Lewis and Clark Lake, South Dakota was modified due to the findings presented herein, in that receivers were stationed in nearshore locations presumably sheltered from the wind. In general, our data support placing receiver stations nearer to shore and protected from wind fetch to the best extent possible to optimize detection distance.